The Analysis Of Moral Value In Everest Movie - Ramli; Firman (JURNAL PENDIDIKAN BAHASA, 2017)
The purposes of this research are divided into two parts. The first purpose of this research is to analyze the moral values in the movie. The second purpose is to know the impact of moral value in toward daily life. To analyze those, the writer used the movie and some related books as the source of the data. The researcher watched the movie and read the script to collect the data and then analyze the data. The result of this research is there are some of moral values in this movie. From the analysis, it can be concluded that there are love and affection, honesty, bravely, kind and friendly, sensitive and not selfish, sorry and apologize, peace ability, loyalty and trustworthy, self - discipline and moderation, confidence and potential. The achievements of this research are expected to give some contributions to further study of moral values like the positive things can learn in the movie. Theoretically, This research is also hoped to be studied by students, lecturers, or other people who will be the interested to the movie. Practically, to contribute the development of literary study, particularly among the people who are interested in the literary study, To remind readers the importance of moral values and also implements it in daily activity